Risk Mitigation, Vulnerability Management and Resilience under Disasters - Sapountzaki, Kalliopi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue (SI) discusses the topic of Disaster Risk Management and its cornerstones: vulnerability reduction and resilience building. The focus of the SI is the impact of risk information, communication and representation, risk knowledge as related to science and practice, risk perception and awareness, and risk culture on multi-faceted vulnerability and several aspects of resilience.